Response of Sunflower to Nitrogen and Phosphorus in North Dakota. (1st March 2018) - Schultz, Eric; DeSutter, Thomas; Sharma, Lakesh; Endres, Gregory; Ashley, Roger; Bu, Honggang; Markell, Samuel; Kraklau, Austin; Franzen, David
Abstract : Core Ideas: Nitrogen availability and fertilization can increase sunflower see yield. Nitrogen fertilization may decrease oil concentration of oilseed sunflower. Nitrogen fertilization increases sunflower lodging risk in windy regions. The N and P recommendations for sunflowers growers in North Dakota have not been changed in 30 yr. Twenty‐two N and P rate experiments were conducted during 2014 and 2015. The objective was to determine the response of seed yield, oil concentration, and lodging to available N and P. In 2014 studies were a randomized complete block split plot with N rate as main plots and P rate as subplots. Nitrogen was applied at rates of 0, 45, 90, 134, 179, and 224 kg N ha −1 . Phosphorus was applied to establish P rates of 0, 13, 26, and 39 kg P ha −1 . In 2015, the field design included only 0 and 26 kg P ha −1 . Experiments were taken to yield and lodging was recorded at harvest. Oil seed sunflower (17 experimental locations) was also analyzed for oil concentration. The N response of sunflower seed yield was quadratic. Increased N rate resulted in lower oil concentration in half of the oilseed experiments. Increased N rate was linearly related to increasing lodging at several sites. Phosphate fertilization had little effect on seed yield, oil concentration, and lodging, despite many of the sites having soil P levels considered 'low'. Future N rate recommendations should be based on seed yield response with increasing N and oil concentration reduction with increasing N for oilseed sunflower. A limit to maximum N rate should also be considered because of the lodging risk in this wind‐plagued region.